Time Estimation of Onion Leaf Drying - Mohammad Djaeni (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
The main process of the onion post harvest treatment is drying proces. High moisture content of onion leaf and outer layer of onion must be reduced up to moisture content 12% or below (wet basis). This level keeps onion being still fresh. The conventional drying with direct sunlight still has been widely used because of the cheap process. However, this technique needs too long drying time as well as climate dependency. This research evaluated convective dryer for onion leaf drying. The mass transfer coefficient, and moisture diffusivity was estimated to predict effective drying time. Results show that the drying time was shorter as the temperature and air velocity increased. For example, at 60oC and air velocity 0.5 m.s-1, the drying time was about 19 hours. The drying time can be can be 5hours shorter at higher air velocity. In addition,with increase of air velocity, the drying time can be also speeded up, significantly. Here, the air temperature must be kept at maximally 60oC in order to avoid onion degradation. Therefore, the increase of air velocity is a good option to shorten drying time and retain the quality.